Challenging misrepresentations of black womanhood : media, literature and theory - Gammage, Marquita Marie, 1983-; Alameen-Shavers, Antwanisha (London : Anthem Press, 2019)
'Challenging Misrepresentations of Black Womanhood' investigates the stereotyping of Black womanhood and the larger sociological impact on Black women. The text details the historical and contemporary use of stereotypes against Black women and how Black women work to challenge and dispel false perceptions.
<span data-sheets-value="{"1":2,"2":"List of Tables and Figures; Acknowledgements; Introduction, Marquita Gammage; Part I: Historical Conceptualizations; Historical Miseducation on Black Womanhood, Donnetrice Allison; Part II: Motherhood and Mother-Right under Question; The Virility of the Haitian Womb: The Biggest Threat to the Dominican Right, Daly Guilamo; "Black Women Are Genius!": The Image of Celebrated Black Motherhood in Stand-Up Comedy?, Antwanisha Alameen-Shavers; Self-Perceptions and Strategies of Self-Determination among Black Women Student Parents on Campus, Sureshi M. Jayawardene and Serie McDougal III; Part III: Media, Literature and Public Perceptions of Black Womanhood; Exploring Contemporary Stereotypes of Black Womanhood in Claudia Rankine's 'Citizen: An American Lyric', Raquel Kennon; Ladyhood in Distress: Black Politics in Nicole Sconiers's 'Escape from Beckyville', Jalondra A. Davis; Representing the Black Woman as Immoral and Abandoning the Black Family: A Cultural Analysis of 21st Century Television Dramas Starring Black Women, Marquita Gammage; Part IV: Politics and Public Implications; Sapphires Gone Wild: The Politics of Black Women's Respectability in the Age of the Ratchet, De Anna J. Reese and Delia C. Gillis; Michelle Obama Laughs: Political Meme Warfare and the Regurgitation of the Mythological Black Woman, Kiedra Taylor; Part V: Advocacy, Activism and Affirmation of Black Womanhood; Kawaida Womanism as an Interpretative Framework for Understanding Africana Womanhood: Analyzing African American Women's Self-Perceptions, Marquita Gammage; List of Contributors; Index."}" data-sheets-userformat="{"2":771,"3":{"1":0}, "4":{"1":2,"2":16777215}, "11":3,"12":0}">List of Tables and Figures; Acknowledgements; Introduction, Marquita Gammage; Part I: Historical Conceptualizations; Historical Miseducation on Black Womanhood, Donnetrice Allison; Part II: Motherhood and Mother-Right under Question; The Virility of the Haitian Womb: The Biggest Threat to the Dominican Right, Daly Guilamo; "Black Women Are Genius!": The Image of Celebrated Black Motherhood in Stand-Up Comedy?, Antwanisha Alameen-Shavers; Self-Perceptions and Strategies of Self-Determination among Black Women Student Parents on Campus, Sureshi M. Jayawardene and Serie McDougal III; Part III: Media, Literature and Public Perceptions of Black Womanhood; Exploring Contemporary Stereotypes of Black Womanhood in Claudia Rankine's 'Citizen: An American Lyric', Raquel Kennon; Ladyhood in Distress: Black Politics in Nicole Sconiers's 'Escape from Beckyville', Jalondra A. Davis; Representing the Black Woman as Immoral and Abandoning the Black Family: A Cultural Analysis of 21st Century Television Dramas Starring Black Women, Marquita Gammage; Part IV: Politics and Public Implications; Sapphires Gone Wild: The Politics of Black Women's Respectability in the Age of the Ratchet, De Anna J. Reese and Delia C. Gillis; Michelle Obama Laughs: Political Meme Warfare and the Regurgitation of the Mythological Black Woman, Kiedra Taylor; Part V: Advocacy, Activism and Affirmation of Black Womanhood; Kawaida Womanism as an Interpretative Framework for Understanding Africana Womanhood: Analyzing African American Women's Self-Perceptions, Marquita Gammage; List of Contributors; Index.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed March 13, 2019).
JSTOR
Keywords: African American women -- Social conditions; African Americans in mass media; Women in mass media; African American women in literature; African American women in popular culture; Noires américaines -- Conditions sociales; Noirs américains dans les médias.; Femmes dans les médias.; Noires américaines dans la culture populaire; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; SOCIAL SCIENCE -- Women's Studies; African American women in literature; African American women in popular culture; African American women -- Social conditions; African Americans in mass media; Women in mass media; Electronic book